Aortic Arch Calcification as a Predictor of Repeated Arteriovenous Fistula Failure within 1-Year in Hemodialysis Patients. (31st May 2017) - Yap, Yit-Sheung; Ting, Kai-Ting; Chi, Wen-Che; Lin, Cheng-Hao; Liu, Yi-Chun; Kuo, Po-Lin; Chuang, Wan-Long
Abstract : Objectives . The aim of the study was to identify the factors associated with repeated arteriovenous fistula (AVF) failure within 1-year, especially the impact of aortic arch calcification (AAC) on patency of AVF. Materials and Methods . We retrospectively assessed chest radiography in hemodialysis patients who had undergone initial AVF. The extent of AAC was categorized into four grades (0–3). The association between AAC grade, other clinical variables, and repeated failure of AVF was then analyzed by binary logistic regression analysis. Results . This study included 284 patients (158 males, mean age 61.7 ± 13.1 years). Patients with higher AAC grade were older, had more frequently diabetes mellitus and cardiovascular disease, had lower diastolic blood pressure, and had higher corrected calcium and lower intact parathyroid hormone levels. In multivariate analysis, the presence of higher AAC grade (odds ratio (95% confidence interval): 2.98 (1.43–6.23); p = 0.004 ), lower mean corrected calcium (p = 0.017 ), and mean serum albumin level (p = 0.00 8 ) were associated with repeated failure of AVF. Conclusions . The presence of higher AAC grade, lower mean corrected calcium and mean serum albumin level were independently associated with repeated AVF failure within 1 year in hemodialysis patients.